Effect of cleaning robot's moving shadow on PV string. (April 2023) - Figgis, Benjamin; Bermudez, Veronica; Garcia, Juan Lopez
Highlights: Field test of cleaning robot's moving shadow on operating PV string. Much larger power drop for landscape modules than portrait. Larger power drop for full-cell modules than half-cut. No cell hotspots created. Bypass diode heated when module stopped, but not while moving. Abstract: PV cleaning robots cast a shadow on the PV modules which they are cleaning, if used in daylight. The shadow affects the electrical characteristics (current and voltage) of the module string, and could potentially also create hot spots in modules' cells or bypass diodes. The severity of these effects depends on the layout of cells and bypass diodes and the module's orientation, among other factors. In this study we tested a commercial cleaning robot on strings of two kinds of PV modules with different cell formats, connected to a grid-tied inverter. It was found that the string power was greatly reduced when modules were in landscape orientation, but barely affected in portrait orientation. The robot shadow caused slightly greater power reduction for full-cell than half-cut modules. While the robot was in motion, no heating of cells or bypass diodes was observed, although diode heating did occur if the robot stopped on a module. For the worst case of full-cell landscape modules, a simplified estimate of the energy loss due to one robot pass was roughly equivalent to 0.16% of the string's daily energy production. The results suggest that if PV cleaning robots are used in daylight, the power loss from their shadow could be almost eliminated by installing modules in portrait orientation.